Is Allergic Rhinitis Related to Otitis Media with Effusion in Adults and Children? Applying Epidemiological Guidelines for Causation - Ioannis Michael Vlastos; Natalia Tsotsiou; Mohannad Almomani; Maria Doulaptsi; Alexandros Karatzanis; Emmanuel Prokopakis (Cells)
This review studies the potential relationship between the pathogenesis of allergic rhinitis (AR) and otitis media with effusion (OME) in both adults and children, applying the modified Bradford Hill criteria. While AR and OME are distinct conditions, several epidemiological and experimental studies suggest a significant association, primarily through allergic mechanisms such as Th-2 immune responses, Eustachian tube dysfunction, and inflammatory mediators in the middle ear. Given the substantial diversity and, in many instances, the “low quality” of related studies when assessed against the standards of modern evidence-based medicine, employing a structured framework like the modified Bradford Hill criteria is beneficial for investigating and establishing causality. This approach, which allows a wide range of diverse studies to be classified as direct, mechanistic, or parallel evidence, supports the notion that management of the allergic immune response may improve OME outcomes, although the inconsistencies among studies require further research. Despite current guidelines recommending against the use of antiallergic medications, the application of the above criteria suggests that proper diagnosis and treatment of allergic rhinitis should be strongly considered in adults and children with OME.